2020
DOI: 10.1101/2020.06.29.178855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secondary single-cell transcriptomic analysis reveals common molecular signatures of cerebrovascular injury between traumatic brain injury and aging

Abstract: AbstractCerebrovascular injury is a common pathological feature of a spectrum of neurological disorders including traumatic brain injury (TBI), stroke, Alzheimer’s disease (AD), as well as aging. Vascular manifestations among these conditions are similar indeed, including the breakdown of the blood-brain barrier (BBB). However, whether there is a common molecular mechanism underlying the vascular changes among these conditions remains elusive. Here, we report secondary transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…Our data demonstrate the power of time course evaluations to chart the course of transcriptomic sequalae caused by experimental TBI. Our findings recapitulate several previously published observations 5,8,11,12,37 . Of note, the signatures identified here differ substantially between the genes that are induced (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data demonstrate the power of time course evaluations to chart the course of transcriptomic sequalae caused by experimental TBI. Our findings recapitulate several previously published observations 5,8,11,12,37 . Of note, the signatures identified here differ substantially between the genes that are induced (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Measurement of the perturbations in gene expression in bulk tissue and single cells following TBI in model systems has provided a systems-level perspective of the impacts of TBI [8][9][10][11][12] . In the initial period following TBI, transcriptional studies have identified signatures of neuroinflammation, and cell death, that correlate with long-term outcomes such as cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%